Q: 5x plus 3y equals 17 5x - 2y equals -3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

9y-3y=6y; 6y+2y=8y; so your answer is 8y

y = -1

4n + 3y

are you talking about a system of equations where x+3y=-7 -x+2y=-8 if so, then the answer is {2,-3}

(-1, 0)

Related questions

3y - 3 = 2y + 5 3y - 2y = 5 + 3 y = 8

5y-2y= 3y+2 5y-2y-3y= 2 0y= 2

2y + 3 = 3y + 9 2y - 3y = 9 - 3 or -y = 6 so y = -6

The expression 3y + 2y + y simplifies to 6y. This is because when you add like terms (terms with the same variable, in this case y), you add the coefficients (numbers in front of the variable) together. In this case, 3y + 2y = 5y, and then adding another y gives you 6y.

9y-3y=6y; 6y+2y=8y; so your answer is 8y

If 3y = 12, 2y = 8

y = -1

4n + 3y

are you talking about a system of equations where x+3y=-7 -x+2y=-8 if so, then the answer is {2,-3}

3y + 2y + 4 + 1 = 805y + 5 = 805y = 75y = 15

(-1, 0)

80 = 3y + 2y + 4 + 1 75 = 5y 15 = y y = 15